Efektivitas Bimbingan Kelompok Dengan Teknik Problem Solving Terhadap Peningkatan Self Disclosure - Laela Nabita Irawan; Sabar Lesmana; Dwi Endrasto Wibowo (Guidance : Jurnal Bimbingan dan Konseling, 2022)
This study aims to test the effectiveness of group guidance services with techniques problem solving to improve self-disclosure for class XI students at Tridaya Sakti SMK Bekasi. This research uses a quantitative approach, the type of this research is Quasi Experimental Design with the form of Nonequivalent Control Group Design. This study involved students of class XI at SMK Tridaya Sakti Bekasi. Based on the results of observations and the distribution of thescale instrument self-disclosure, it shows that behavior self-disclosure students'at the time of the exam is categorized as low. The population is 136 students and the sample is 20 students, 10 students in the experimental group and 10 students in the control group. The sampling technique used was purposive sampling. The data analysis technique used was the T-test with the help of the SPSS Windows version 25 program. The results showed an increase in behavior self-disclosure students' after being given Problem Solving treatment , the sig value was obtained. (2-tailed) of 0.000 < 0.05 and when viewed from tcount = 7,686 and ttable = 2.262 seen from (df) 9 with a significant 0.05 that tcount > ttable means that Ho is rejected and Ha is accepted. Thus, it can be concluded that group guidance services with techniques are problem solving effective in increasing self-disclosure for class XI students of SMK Tridaya Sakti Bekasi